Rapid Resolution of Large and Non- Resolving Corneal Hydrops using a modified technique of compression sutures. (4th July 2022) - Chaurasia, Sunita; Ramappa, Muralidhar; Murthy, Somasheila
ABSTRACT: Purpose: To report rapid resolution of corneal clearing with the application of a modified technique of compression sutures in large hydrops. Methods: Interventional case series of seven patients. Results: Three patients had acute hydrops secondary to keratoconus, three had pellucid marginal corneal degeneration and another one had ectasia of undetermined etiology. A thorough slit-lamp evaluation and anterior segment optical coherence tomography was performed. The surgical technique involved paracentesis, anterior chamber decompression, compression suture placement within the stroma against the background of partial air fill in the anterior chamber, and bandage contact lens application. All eyes showed a remarkable reduction in corneal edema at 1 h (documented in four eyes) and 1 day (documented on the rest), which continued to improve in further follow up. Conclusions: The modified technique of compression sutures facilitate rapid recovery of corneal edema in acute hydrops seen in keratoconus and pellucid marginal corneal degeneration. The physiologic basis is akin to the external tamponade achieved with buckle in retinal detachment surgeries.